The Impact of exercise endurance the forms of unlimited and relative force on some of the functional abilities and on 800 m running - Allaw, Abduljabbar Kareem; Jaffer, Ammar Mosa; Ahmed, mar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The research involves five chapter . The first chapter dealing with the definition of the research . The chapter also explain the effect of the practice system on each part of human body in general regardless the body weight ( this means un limited practice ) for these parts and the effect on the whole body . Also we can use body weight practice system , in other words the ability of one part of the body through the other parts . This considered as ( relative practice ) for the whole body . The importance of the induration and suggested practice in order to develop and gain positive results . The research problem lies the present curriculum that don not take care the present classification ( un limited force ) ( relative force ( The research aimsTo identify the body ability . ( speed endurance , force endurance , performance, and speed ) and some symbols of young runner for 800m . Design special practice to develop the ability by two systems. ( un limited force ) ( relative force endurance system ) To identify the difference between the result of the two systems to develop the ability in this research The differences include the following There are differences which have static sense between the previous and next test results that curriculum with the functional signs for both groups their performance. there are differences which have static senses between tests results of force endurance and some function signs.